RANKL immunisation inhibits prostate cancer metastasis by modulating EMT through a RANKL-dependent pathway - Mineon Park (Nature Portfolio, 2021)
Abstract Prostate cancer (PCa) morbidity in the majority of patients is due to metastatic events, which are a clinical obstacle. Therefore, a better understanding of the mechanism underlying metastasis is imperative if we are to develop novel therapeutic strategies. Receptor activator of nuclear factor kappa-B (NF-κB) ligand (RANKL) regulates bone remodelling. Thus, agents that suppress RANKL signalling may be useful pharmacological treatments. Here, we used preclinical experimental models to investigate whether an inactive form of RANKL affects bone metastasis in RANKL-induced PCa. RANKL was associated with epithelial–mesenchymal transition (EMT) and expression of metastasis-related genes in PC3 cells. Therefore, we proposed a strategy to induce anti-cytokine antibodies using mutant RANKL as an immunogen. RANKL promoted migration and invasion of PC3 cells through EMT, and induced a significant increase in binding of β-catenin to TCF-4, an EMT-induced transcription factor in PCa cells, via mitogen-activated protein kinase and β-catenin/TCF-4 signalling. Thus, RANKL increased EMT and the metastatic properties of PC3 cells, suggesting a role as a therapeutic target to prevent PCa metastasis. Treatment with mutant RANKL reduced EMT and metastasis of PC3 PCa cells in an experimental metastasis model. Thus, mutant RANKL could serve as a potential vaccine to prevent and treat metastatic PCa.